PENGARUH LITERASI KEUANGAN DAN KONTROL DIRI TERHADAP PERILAKU PENGELOLAAN KEUANGAN MAHASISWA - Royani, Sri; Syahrudin, Husni; Kuswanti, Heni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study investigates the impact of financial literacy and self-control on financial management behavior. Employing a a correlational research design with quantitative approach, the research focuses on a population of 237 students enrolled in the Economics Education program at FKIP Untan, specifically from the 2021-2024 cohort. This research sample used probability sampling techniques with simple random sampling method and produced a sample of 150 students. The analysis methods utilized in this study include descriptive statistics, T-tests, F-tests, multiple linear regression, and the coefficient of determination. The findings reveal that: 1) financial literacy (X1) does not have a..significant partial effection financial management-behavior (Y); 2) self-control (X2) does exert a significant partial effect on financial management behavior (Y); and 3) there is a simultaneous effect of both financial literacy (X1) and self-control (X2) on financial management behavior (Y). The coefficient of determination calculated is 0.538, shows that the contribution of variable X1 and variable X2 in explaining or predicting variable Y is 53,8%. Future researchers are encouraged to explore a broader range of variables, including lifestyle factors, pocket money, income, and other relevant influences.